2020
DOI: 10.1200/jco.2020.38.15_suppl.4005
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II/III trial comparing hepatectomy followed by mFOLFOX6 with hepatectomy alone for liver metastasis from colorectal cancer: JCOG0603 study.

Abstract: 4005 Background: The role of adjuvant chemotherapy after hepatectomy is controversial for liver only metastases from colorectal cancer (LM). Current recommendations for oxaliplatin-containing adjuvant regimen (FOLFOX) for LM are based on extrapolation of the results of the EORTC intergroup trial 40983, which showed that perioperative FOLFOX confirmed a progression-free survival benefit but did not affect overall survival (OS) in LM patients. We conducted a randomized controlled trial to determine if adjuvant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 0 publications
3
20
0
Order By: Relevance
“…Previously, recurrence after resection of CLM was often considered to occur in the residual liver, but in this study, all cases of recurrence involved extrahepatic metastasis. This was also observed in JCOG0603, in which 66% of recurrent cases in the adjuvant FOLFOX arm were extrahepatic metastases [6]. The very low recurrence of residual liver metastasis in our study suggests that CAPOX as postoperative adjuvant chemotherapy for CLM may suppress the recurrence of metastasis to residual liver.…”
supporting
confidence: 84%
“…Previously, recurrence after resection of CLM was often considered to occur in the residual liver, but in this study, all cases of recurrence involved extrahepatic metastasis. This was also observed in JCOG0603, in which 66% of recurrent cases in the adjuvant FOLFOX arm were extrahepatic metastases [6]. The very low recurrence of residual liver metastasis in our study suggests that CAPOX as postoperative adjuvant chemotherapy for CLM may suppress the recurrence of metastasis to residual liver.…”
supporting
confidence: 84%
“…Recently, a Japanese group presented results of the JCOG0603 at ASCO 2020, in which patients with resected liver metastases were randomized to observation or adjuvant chemotherapy with FOLFOX6m × 12 cycles, in a phase III trial. This trial demonstrated a benefit of adjuvant FOLFOX6m for disease-free survival (DFS 1.7 years vs. 4.3 years, HR 0.67 (0.5–0.92)) but no benefit for overall survival (5-year OS 83% vs. 71%, HR 1.25 (0.78–2)) in this subgroup of patients [ 40 ]. Adjuvant treatment with irinotecan in patients with CRC after liver surgery was not shown to be superior to 5FU/LV in a phase III study [ 41 ].…”
Section: Treatment Of Patients With Resectable Liver Colorectal Metastases (Liver M1: Number <4 and Size <5 Cm)mentioning
confidence: 99%
“…The role of perioperative chemotherapy with FOLFOX4 was evaluated in the EORTC intergroup trial 40,983 (EPOC). This study clearly demonstrated that perioperative FOL-FOX4 therapy (6 cycles before surgery and 6 cycles after) significantly improved PFS compared to surgery alone in CRC patients with resected liver metastases [46].…”
Section: Treatment Of Patients With Resectable Liver Colorectal Metastases (Liver M1: Number <4 and Size <5 Cm)mentioning
confidence: 99%
“…In the EORTC 40983 trial, perioperative chemotherapy was associated with 7.3% absolute increase in 3-year progression-free survival, however there was no difference in overall survival [29,30]. Another Japanese study also did not show overall survival benefit with adjuvant chemotherapy [31]. Given the established role of adjuvant therapy in stage III colon cancer, despite lack of strong evidence many expert groups support perioperative or postoperative chemotherapy for resectable colorectal cancer metastases.…”
Section: Role Of Adjuvant Therapy For Resected Colorectal Cancer Metamentioning
confidence: 99%